2021
DOI: 10.3390/diagnostics11060941
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Antibodies Testing in Recipients of COVID-19 Vaccination: Why, When, and How?

Abstract: Although universal vaccination is one of the most important healthcare strategies for limiting SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) circulation and averting the huge number of hospitalizations and deaths due to coronavirus disease 2019 (COVID-19), significant inter-individual variability of COVID-19 vaccines’ efficacies has been described, mostly due to heterogeneous immune response in recipients. This opinion paper hence aims to discuss aspects related to the opportunity of monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 70 publications
5
49
0
Order By: Relevance
“…In conclusion, the results of our study extend the evidence provided by Tré-Hardy et al 1 that total anti-SARS-CoV-2 S antibodies levels tend to decline at 3 months after the first vaccine dose, though we also showed that such decline occurs in both baseline seropositive and seronegative subjects, and with serum levels that tend to be significantly lower in older subjects. These findings not only confirm the importance of serological testing for monitoring the immunogenic response after vaccination, 4 but provide further support to the conclusion that personalization of COVID-19 vaccine administration, with use of further boosters, may be advisable in selected categories of the population.…”
supporting
confidence: 71%
“…In conclusion, the results of our study extend the evidence provided by Tré-Hardy et al 1 that total anti-SARS-CoV-2 S antibodies levels tend to decline at 3 months after the first vaccine dose, though we also showed that such decline occurs in both baseline seropositive and seronegative subjects, and with serum levels that tend to be significantly lower in older subjects. These findings not only confirm the importance of serological testing for monitoring the immunogenic response after vaccination, 4 but provide further support to the conclusion that personalization of COVID-19 vaccine administration, with use of further boosters, may be advisable in selected categories of the population.…”
supporting
confidence: 71%
“… 47 , 48 Although the half-life of antibodies elicited by COVID-19 vaccines is still being analyzed, it is suggested that they may last as long as 6–8 months. 49 , 50 , 51 , 52 We have studied the humoral immune kinetics of anti-RBD antibodies elicited by SPUTNIK V up to 180 days post-vaccination and found that although anti-RBD titers begin to drop 60 days after vaccination, antibodies are still present in 94.6% of volunteers at 90 dpv ( Fig. 1 c).…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating things, CVID patients are known to be able to even produce antibodies at normal titers, but these antibodies may have poor avidity with impaired opsonophagocytic function 7 . Likewise, comparing serum levels of anti-SARS-CoV-2 antibodies between CVID patients and immunocompetent subjects to evaluate the magnitude of vaccination efficacy may as well be meaningless, since the level of neutralizing antibodies required to confer protection has not been definitively established 8 . Indeed, serum levels of anti-SARS-CoV-2 antibodies appeared to be overall more elevated in healthy hospital personnel than in CVID patients, but, again, the clinical significance of this difference is currently unknown 8 .…”
mentioning
confidence: 99%
“…Likewise, comparing serum levels of anti-SARS-CoV-2 antibodies between CVID patients and immunocompetent subjects to evaluate the magnitude of vaccination efficacy may as well be meaningless, since the level of neutralizing antibodies required to confer protection has not been definitively established 8 . Indeed, serum levels of anti-SARS-CoV-2 antibodies appeared to be overall more elevated in healthy hospital personnel than in CVID patients, but, again, the clinical significance of this difference is currently unknown 8 . Interestingly, the only patient (#4) with prior, naturally-acquired immunization against SARS-CoV-2 had an impressive rise in the titers of neutralizing antibodies following vaccination; thus, if prior immunization is a prerequisite for remarkable antibody responses following vaccination, it may theoretically be anticipated that a further vaccine jab would probably significantly enhance the protective antibody response in the remaining patients as well.…”
mentioning
confidence: 99%